Sense of coherence, its meaning and coping with stress among people after orthopedic surgery - Kotowska, Joanna; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2019)
Aim: Assessment of the sense of coherence, methods of coping with stress and the relationship between their components among people after orthopedic surgery.Materials and methods: 100 people were examined. The proper group consists of 50 patients after orthopedic surgery. The control group consists of 50 healthy people. All the subjects completed a questionnaire with questions about basic metrical data and two standardized questionnaires: SOC-29 and Mini-COPE. The results underwent statistical analysis.Results: Both groups did not differ in the level of the sense of coherence, the distribution was notably similar to normal (p > 0,05). However, the differences in the strategies of coping with stress were observed. Differences in correlations between individual coherence components and remediation strategies have also been noticed.Conclusions: The patients were characterized by a greater intensity of non-constructive coping strategies compared to the control group. Only among them the stronger sense of coherence coexisted with lower inclinations to negative patterns of behavior. Higher global life orientation was associated with a more favorable and positive approach to problems among healthy people.